2019
DOI: 10.1007/s40279-019-01215-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of School-Based Interventions for Improving Muscular Fitness Outcomes in Adolescent Boys: A Systematic Review and Meta-analysis

Abstract: Background It has been reported that boys' and girls' physical activity (PA) levels decline throughout adolescence. Boys are at risk of physical inactivity during adolescence; however, in intervention research, they are an under-represented group relative to girls. It is suggested that the school environment may be central to developing interventions that support adolescents in meeting the current PA guidelines. The aim of this systematic review and meta-analysis was to investigate the efficacy of school-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 100 publications
2
35
0
Order By: Relevance
“…Overall, intensity was increased across the 16 weeks such that during weeks 1-5; 16-20 RM with 30 seconds rest between sets, in weeks 6-10; between 8-14 RM, with between 30-120 seconds inter-set rest, and in weeks [11][12][13][14][15][16]; between 6 and 12 RM with 30-120 seconds inter-set rest. For the multigym exercises (Table 1) load was adjusted by re-estimated participant's 1 RM according to the load and repetitions performed during the last session of the training block, whereas exercises in the free-weight and functional/proprioceptive categories were progressed in a more informal way by estimating adding load to try and maintain participants within the target repetition range.…”
Section: Plos Onementioning
confidence: 96%
See 1 more Smart Citation
“…Overall, intensity was increased across the 16 weeks such that during weeks 1-5; 16-20 RM with 30 seconds rest between sets, in weeks 6-10; between 8-14 RM, with between 30-120 seconds inter-set rest, and in weeks [11][12][13][14][15][16]; between 6 and 12 RM with 30-120 seconds inter-set rest. For the multigym exercises (Table 1) load was adjusted by re-estimated participant's 1 RM according to the load and repetitions performed during the last session of the training block, whereas exercises in the free-weight and functional/proprioceptive categories were progressed in a more informal way by estimating adding load to try and maintain participants within the target repetition range.…”
Section: Plos Onementioning
confidence: 96%
“…Little is known however regarding the implementation and outcomes of resistance training interventions in low-middle income countries. The majority of studies have been conducted in high-income countries [15,16], and a recent systematic review of resistance training programs in schools showed that only 1 of 11 studies was implemented in an low-middle income country [15]. School represents the ideal setting for the delivery of resistance training as it provides opportunities to introduce students to novel forms of activity they might not be exposed to outside of school [17].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended minimum level of physical activity for adolescents is moderate to vigorous activity for at least 20 min per session, three times a week [ 7 ]. Several studies have proposed school-based physical activity programs to encourage physical activity in adolescents, as schools are an ideal environment for implementing physical activity programs, and these programs are known to be effective in promoting physical fitness [ 8 , 9 , 10 ]. In addition, adolescents are most active during school days, and schools provide access to physical activities in a manner that is independent of academic background or socioeconomic status [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have proposed school-based physical activity programs to encourage physical activity in adolescents, as schools are an ideal environment for implementing physical activity programs, and these programs are known to be effective in promoting physical fitness [ 8 , 9 , 10 ]. In addition, adolescents are most active during school days, and schools provide access to physical activities in a manner that is independent of academic background or socioeconomic status [ 8 , 11 ]. Furthermore, school-based physical activities ensure the exposure of a maximum number of adolescents to the intervention, and it is relatively easy to increase the number of adolescents participating in these activities.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Booth, Rowlands, and Dollman [13], there is little evidence of the decrease in PA among children and adolescents. Moreover, interventions for improving muscular fitness in adolescent boys demonstrated small-to-moderate effects [14].…”
Section: Introductionmentioning
confidence: 99%